(untitled) (Research, Society and Development, 2021)
Objective: to point the quality of life of children and adolescents with cancer from studies that applied the PedsQL 3.0 Cancer Module and describe the score found in these studies. Methodology: Systematic literature review in the databases Medline, LILACS, Scielo, Scopus, PsycINFO, Science Direct and Web of Science of studies published between 2015 and 2020. Results: 18 articles were selected, where it was observed that Leukemia was the most frequent type of cancer in 78% of the studies. Chemotherapy was the treatment received in 55% of the research and in relation to the average score of the participants, it is found that the scores ranged from 59.1 to 74.53. Conclusion: The mean score ranged from 59.1 to 74.53. The type of cancer seems to have no significant influence on the scores. Fatigue is the symptom most associated with low quality of life scores. And patients treated with chemotherapy tend to have lower quality of life scores.